Reformulation of the Mechanism for Imposing Criminal Sentences for Narcotics Crimes in Indonesia - Iqbal Taufik; Muhammad Irham; Nasarudin Tianotak; Andres Deny Bakarbassy (Faculty of Law, Universitas Pekalongan, 2025)
Equality before the law, in its implementation, does not only refer to the actions of the state toward its citizens, but also to actions that aim to ensure legal certainty based on justice. Equality in legal protection and law enforcement for victims of narcotics crimes has not yet been reflected in any tangible form of implementation. Fair sentencing in narcotics-related crimes has become more of a slogan for the public rather than a reality for individuals who are subjected to the death penalty for narcotics abuse. Through normative legal research, it was found that the presence of Ad Hoc judges as assessors and final decision-makers on the recommendations of the integrated assessment team for rehabilitation reflects justice based on the principle of equality before the law in handling victims of narcotics crime.